Real-time driver activity detection using advanced deep learning models - Md. AL Emran; Md. Ariful Islam; Md. Obaydullahn Khan; Md. Jewel Rana; Saida Tasnim Adrita; Md. Ashik Ahmed; Mahmoud M. A. Eid; Ahmed Nabih Zaki Rashed (Cognitive Neurodynamics, 2026)

Predicting hydrodesulfurization reactivity of middle distillates for producing ultra-low-sulfur diesel - Xiaoliang Ma; Hamza Albazzaz; Muhieddine A. Safa; Ahmed M. Al-Otaibi; Narjes Ghaloum; Rashed Bouresli; Shibu Jose; Ashraf M. Kamel (Fuel, 2026)

Ziziphus spina-christi as a natural feed supplement for sustainable livestock nutrition: An updated narrative review - Youssef A. Attia; Asmaa F. Khafaga; Ayman E. Taha; Islam M. Youssef; Khalid A. Asiry; Adel D. Al-Qurashi; Omer H.M. Ibrahim; Khaled H. El-Kholy; Rashed A. Alhotan; Salem R. Alyileili; Sara H.M. Hassab; Mohamed A. Al-Banoby; et al. (Livestock Science, 2026)

Morphogenesis of perithecia and rosette-like ascospores in Sordaria sclerogenia reveals virulence-associated metabolites and ultrastructural mechanisms of root invasion in lemon - Safaa A.M. Yousef; Motrih Al-Mutiry; Wael F. Shehata; Enas A. Almanzalawi; Tahani M. Alqahtani; Samiyah S. Al-Zahrani; Sarah Al-Rashed; Yasser S. Mostafa; Saad A. Alamri; Mohamed A. Abou-Zeid (Physiological and Molecular Plant Pathology, 2026)

A review on gut microbiota and migraine severity: a complex relationship - Noha M. Gamil; Rana M. Ghorab; Reham Z. Elsadawy; Nada M. Khadrawy; Mohamed Abdelhamid; Khalid A. Ismael; Omar A. Mohamed; Mohamed M. Ata; Habiba T. Jalal; Joumana E. Zeidan; Reem T. Rashed; Riham A. El-Shiekh (Inflammopharmacology, 2026)
The gut-brain axis plays a vital role in migraine pathophysiology. Studies highlight reciprocal interactions between the central nervous system and the gastrointestinal tract. Previous research suggests that factors such as gut microbiota profiles, inflammatory mediators, neuropeptides, serotonin pathways, stress hormones, and nutritional substances influence this interaction. The pathophysiology of migraine has been linked to changes in the gut-brain axis, which affects migraine severity and frequency. Additionally, dietary approaches, including the ketogenic diet, vitamin D supplementation, omega-3 intake, probiotics, and weight loss plans, have shown promising effects in reducing migraine symptoms by positively impacting the gut microbiota and the gut-brain axis. Understanding these connections could lead to novel therapeutic strategies for effectively managing migraines. It is worth noting that research highlights several innovative treatments for migraine, such as Zelirex and Cevimide, implantable devices like Cefaly and Revilion, and new effective routes of administration for Sumatriptan. Finally, patients’ perspectives and concerns were thoroughly discussed, with a focus on future directions in the migraine-gut axis research.

Molecular docking and differential rbcl gene expression reveal variation in glyphosate herbicide tolerance of sugarcane varieties - Kawthr S. M. Allam; M. Magdy; A. M. Abd El-Aal; Nasr S. Khalil; M. A. Rashed; A. H. Atta; Reham I. AbdelHamid (Molecular Biology Reports, 2025)

Correction: The potential liver injury induced by metronidazole-provoked disturbance of gut microbiota: modulatory effect of turmeric supplementation - Abdulaziz Q. Ali; Deema Kamal Sabir; Amal F. Dawood; Mohammed Abu-Rashed; Abdulrahman Hasari; Faiz Gharqan; Salem Alnefaie; Lama E. Mohiddin; Maya M. Tatry; Dana A. Albadan; Mohanad M. Alyami; Mohammed F. Almutairi; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Zonisamide nanodiamonds for brain targeting: A comprehensive study utilising in silico, in vitro, in vivo, and molecular investigation for successful nose-to-brain delivery for epilepsy management - Nihal Mohamed Elmahdy Elsayyad; Omar A. Elkady; Mohamed M. Swidan; Hassan M. Rashed; Tamer M. Sakr; Amr M. Abdelhamid; Mai A. Zaafan; Hanan M. El-Laithy (Drug Delivery and Translational Research, 2025)
The blood–brain barrier (BBB) is a stringent barrier that restricts the successful brain delivery of polar neurotherapeutics molecules. One such molecule is Zonisamide (ZNS), a hydrophilic centrally acting anti-epileptic drug. This study aims to overcome the poor ZNS BBB permeability using the nose-to-brain (NTB) carbon-based biocompatible nanodiamonds (ND) delivery system to deliver ZNS directly to the brain, bypassing the BBB, thereby enhancing its efficacy and reducing systemic side effects associated with oral ZNS currently available formulation in clinical practice. Intranasal (IN) ND-ZNS formulations were optimised using an Artificial neuronal network (ANN) and assessed for particle size (PS), zeta potential, loading efficiency (%LE), morphology, and in vitro release. The optimum radiolabelled ND-ZNS complex F1 biodistribution in different organs and its pharmacokinetics were compared to oral and IN-free ZNS in mice. Temporal lobe epilepsy (TLE) model in rats was used to compare the anti-epileptic activity of IN ND-ZNS F1 to IN free ZNS by assessing brain activity, epileptic biomarkers such as (brain neuronal specific enolase (NSE), neurofilament light polypeptide (NEFL), and matrix metallopeptidase-9 (MMP-9)), hippocampal histopathology and the modulatory effect on epigenetic miR-199/SIRT-1 and PVT-1/BDNF pathways. Optimized ND-ZNS complex F1 consists of a ZNS:ND ratio of 1:2 and sonicated for 5 min exhibited the least PS (193.7 ± 19.3 nm), adequate %LE (87.1 ± 9.2%) similar to ANN predictions, with a biphasic in vitro release profile of ZNS, beneficial for both acute and chronic epilepsy treatment. The IN delivery of ND-ZNS complex F1 showed preferential higher in vivo brain uptake with minimal systemic exposure linked with higher brain/blood ratio and significant ( p ≤ 0.05) overall enhanced pharmacokinetics expressed by C max and AUC (0-120min) when compared to oral and IN free ZNS . Moreover, the TLE model confirmed the improved anti-epileptic activity of F1 compared to IN-free ZNS regarding brain activity and hippocampal histopathology, significant suppression of serum NSE, NEFL, MMP-9 levels, miR-199/SIRT-1 pathway, and normalization of PVT-1/BDNF pathway. Therefore, ND used in this study could be a novel, promising carrier to target ZNS directly to the brain via the IN route for effective epilepsy management with less drug dosing and the least systemic side effects. Graphical Abstract

The potential liver injury induced by metronidazole-provoked disturbance of gut microbiota: modulatory effect of turmeric supplementation - Abdulaziz Qaid Ali; Deema Kamal Sabir; Amal F. Dawood; Mohammed Abu-Rashed; Abdulrahman Hasari; Faiz Gharqan; Salem Alnefaie; Lama E. Mohiddin; Maya M. Tatry; Dana A. Albadan; Mohanad M. Alyami; Mohammed F. Almutairi; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Enhancing the nutritional values of egg yolks of laying hens by different dietary sources of omega-3 fatty acids, vitamin e and trace elements - Youssef Attia; Ahmed A.Al Sagan; El-Sayed O.S. Hussein; Marai J. Olal; Tarek A. Ebeid; Abdulaziz A. Alabdullatif; Rashed A. Alhotan; Mohammed M. Qaid; Vincenzo Tufarelli; Gianluca Pugliese; Khaild A. Asiry; Sameer A. Nagadi; et al. (Livestock Science, 2024)

Optical Based Surface Plasmon Resonance Sensor for the Detection of the Various Kind of Cancerous Cell - Shah Ali Rafi; Wahiduzzaman Emon; Ahmed Afif Rafsan; Russel Reza Mahmud; Md. Faysal Nayan; Mahmoud M. A. Eid; Ahmed Nabih Zaki Rashed (Cell Biochemistry and Biophysics, 2024)

Ecological impacts and management strategies of pesticide pollution on aquatic life and human beings - Synan F. AbuQamar; Mohamed T. El-Saadony; Samar S. Alkafaas; Mohamed I. Elsalahaty; Sara S. Elkafas; Betty T. Mathew; Amal N. Aljasmi; Hajar S. Alhammadi; Heba M. Salem; Taia A. Abd El-Mageed; Rashed A. Zaghloul; Walid F.A. Mosa; et al. (Marine Pollution Bulletin, 2024)

Development and Enhancement of PCF-based Sensors for Terahertz-frequency Region Breast Cancer Cell Detection - A. H. M. Iftekharul Ferdous; Laxmi Rani; Md. Safiul Islam; Khalid Sifulla Noor; Sourav Roy; Mahmoud M. A. Eid; Ahmed Nabih Zaki Rashed (Cell Biochemistry and Biophysics, 2024)

Innovative Refractive Index Sensor Utilizing Terahertz Spectrum for Early Cancer Detection: a Photonic Crystal Fiber Approach - A. H. M. Iftekharul Ferdous; Md Naimur Rahman Naim; Khalid Sifulla Noor; Diponkar Kundu; Ahmed Nabih Zaki Rashed (Cell Biochemistry and Biophysics, 2024)

Ameliorative Effects of Zinc Oxide, in Either Conventional or Nanoformulation, Against Bisphenol A Toxicity on Reproductive Performance, Oxidative Status, Gene Expression and Histopathology in Adult Male Rats - Dina M. M. H. El-Kossi; Shawky S. Ibrahim; Kamel M. A. Hassanin; Nashwa Hamad; Noha A. Rashed; Ahmed Abdel-Wahab (Biological Trace Element Research, 2024)
Bisphenol A (BPA) is a widely used endocrine disruptor that represents a significant risk to male reproductive function. Zinc (Zn) is vital for appropriate development of testes and to guarantee optimal testicular function and spermatogenesis. Our goal was to investigate if zinc oxide (ZnO), either in conventional or nanoformulation, could safeguard adult male rats’ reproductive performance against the damaging effects of BPA. Signaling expression of CYP11A1 and Nrf-2 in the testis, testicular oxidant-antioxidant status, Bax/Bcl-2 apoptotic ratio, and histological examination of various reproductive organs were all evaluated. Twenty-eight adult male albino rats were divided randomly into 4 groups (7 animals each) including the control, BPA, conventional zinc oxide (cZnO) + BPA, and zinc oxide nanoparticles (ZnO-NPs) + BPA groups. The study was extended for 2 successive months. Our findings revealed strong negative effects of BPA on sperm cell characteristics such as sperm motility, viability, concentration and abnormalities. Additionally, BPA reduced serum levels of testosterone, triiodothyronine (T3), and thyroxine (T4). Also, it evoked marked oxidative stress in the testes; elevating malondialdehyde (MDA) and reducing total antioxidant capacity (TAC). BPA significantly downregulated testicular mRNA relative expression levels of CYP11A1 and Nrf-2 , compared to control. Testicular apoptosis was also prompted by increasing Bax/ Bcl-2 ratio in testicular tissue. Histopathological findings in the testes, epididymis, prostate gland, and seminal vesicle confirmed the detrimental effects of BPA. Interestingly, cZnO and ZnO-NPs significantly alleviated all negative effects of BPA, but ZnO-NPs performed better. In conclusion, our findings point to ZnO, specifically ZnO-NPs, as a viable treatment for BPA-induced testicular dysfunction.

Effect of dietary electrolyte balance and arginine to lysine ratio on hematological, antioxidant and immunological traits in dual-purpose breeding hens under cyclic heat stress condition - Youssef A. Attia; Ahmed A. Abdallah; Fulvia Bovera; Abd El-Hamid E. Abd El-Hamid; Asmaa Sh El-Naggar; Rashed A. Alhotan; Vincenzo Tufarelli; Reda M. Zaki (Journal of Thermal Biology, 2024)

New bithiophene derivative attenuated Alzheimer’s disease induced by aluminum in a rat model via antioxidant activity and restoration of neuronal and synaptic transmission - Kholoud AbdEl-Raouf; Hussein S.H. Farrag; Rashed Rashed; Mohamed A. Ismail; Monir A. El-Ganzuri; Wael M. El-Sayed (Journal of Trace Elements in Medicine and Biology, 2024)

Cuticular chemical compounds of puparial cases of three forensically important blow flies from Egypt: potential for accurate identification and forensic investigations - Eman E. Zaher; Salwa S. Rashed; Fatma A. Abdel-Halim; Samar M. Mohammed; Abeer M. Salem (International Journal of Tropical Insect Science, 2024)
The distinct and species-specific chemical compounds found on the insect cuticle have demonstrated effectiveness in various applications, including species identification. Accurate identification of fly species becomes challenging when only damaged empty puparial cases are available, making it difficult to use traditional morphological and molecular identification methods. This study aimed to analyze the chemical compositions of puparial exuviae from three forensically and medically important fly species; Lucilia sericata , Chrysomya albiceps , and Chrysomya marginalis . Gas chromatography/mass spectrometry (GC–MS) was employed to assess the chemical profiles of these exuviae and evaluate their accuracy in identifying Dipteran insects. The study revealed the presence of twelve classes of chemical compounds across the three species, with retention times ranging from 18.78 to 35.03. A total of forty-two compounds with chain lengths ranging from C12 to C45 were identified. The profiles of Ch. albiceps and L. sericata displayed similarities, with alcohol being the most abundant compound (28.6%) in L. sericata . However, alkanes, including n-alkanes, branched alkanes, and cycloalkanes, constituted the main components of the cuticles in the three species, with Ch. marginalis displaying the highest percentage. These findings represent an initial step towards utilizing hydrocarbon composition as a practical tool for distinguishing between forensic species in Egypt.

Protective influence of supplementary betaine against heat stress by regulating intestinal oxidative status and microbiota composition in broiler chickens - Ali R. Al Sulaiman; Ala M. Abudabos; Rashed A. Alhotan (International Journal of Biometeorology, 2024)

Exploiting fungi in bioremediation for cleaning-up emerging pollutants in aquatic ecosystems - Synan F. AbuQamar; Hassan I. Abd El-Fattah; Maha M. Nader; Rashed A. Zaghloul; Taia A. Abd El-Mageed; Samy Selim; Belal A. Omar; Walid F. Mosa; Ahmed M. Saad; Khaled A. El-Tarabily; Mohamed T. El-Saadony (Marine Environmental Research, 2023)

Preparation and characterization of nanomuscovite by intercalation method for adsorption of heavy metals from polluted water - M. Nageeb Rashed; A. E Arifien; F. A. El-Dowy (Environmental Geochemistry and Health, 2023)
In this study, nanomuscovite adsorbents were prepared by intercalation with various organic intercalates (DTAB-TTAB-DTPA-PA-PN) and used to remove Cd 2+ and Pb 2+ from polluted water. The best nanomuscovite was prepared using DTPA and muscovite (Muc/DTPA) and characterized by XRD, TEM, EDX, FTIR, and BET surface area. The developed nanoadsorbent was used to remove Cd 2+ and Pb 2+ from polluted water. The effect of various factors, including contact time, adsorbent dosage, solution pH, and temperature, was investigated. The results reveal that the maximum adsorption of Cd 2+ and Pb 2+ was 91.5% and 97%, respectively, at the initial metal concentration 50 ppm, adsorbent dosage 0.2 g, contact time 60 min, solution temperature 25 °C, and pH 6 for Pb 2+ and pH 7 for Cd 2+ . Adsorption isotherm models (Freundlich, Langmuir, Dubunin–Radushkevich, and Temkin isotherm models) as well as kinetic models (pseudo-first-order, pseudo-second-order, Elovich, and intra-particle diffusion models) were employed to evaluate the experimental results. The adsorption of Cd 2+ and Pb 2+ on Muc/DTPA fitted well within the Langmuir isotherm model and followed pseudo-second-order kinetics. Thermodynamics parameters of metal adsorption indicated exothermic and spontaneous processes. Results were applied to the real wastewater that showed high Cd 2+ and Pb 2+ removal.

Characterization and phylogenetic analysis of the complete mitochondrial genome of Mango tilapia (Sarotherodon galilaeus: Cichlidae) - Yosur G. Fiteha; M. A. Rashed; R. A. M. Ali; M. Magdy (Molecular Biology Reports, 2023)
Background Sarotherodon galilaeus (Linné, 1758) is a member of the family Cichlidae, which is considered the most important aquaculture freshwater species endemic to Africa and the Middle East. The genetics and molecular biology of this species are rare. This requires more comprehensive mitochondrial genomes-based phylogenetics to enhance understanding of the relationship and delineate this species. Methods and results Here, we assembled the complete mitogenome of S. galilaeus using Illumina high-throughput sequencing technology. The mango tilapia mitogenome was 16,631 bp in length with an AT composition of 53.4% and 46.4% GC content. It encodes 37 genes comprising two ribosomal RNA genes (rRNAs), 22 transfer RNA genes (tRNAs), and 13 protein-coding genes (PCGs) as well as the D-loop known as the control region. The phylogenetic tree was conducted to provide a relationship within the haplotilapiine lineage based on the maximum likelihood method, and the newly sequenced S. galilaeus was clustered with other Sarotherodon species. Conclusion Our results provide a new perception of the genetic basis of S . galilaeus species for further research on systematics, evolution, population genetics, and molecular ecology.

Mesenchymal Stem Cells and Selenium Nanoparticles Synergize with Low Dose of Gamma Radiation to Suppress Mammary Gland Carcinogenesis via Regulation of Tumor Microenvironment - Omayma A. R. Abozaid; Laila A. Rashed; Sawsan M. El-Sonbaty; Amira I. Abu-Elftouh; Esraa S. A. Ahmed (Biological Trace Element Research, 2023)
Breast cancer is one of the most prevalent and deadliest cancers among women in the world because of its aggressive behavior and inadequate response to conventional therapies. Mesenchymal stem cells (MSCs) combined with green nanomaterials could be an efficient tool in cell cancer therapy. This study examined the curative effects of bone marrow–derived mesenchymal stem cells (BM-MSCs) with selenium nanoparticles (SeNPs) coated with fermented soymilk and a low dose of gamma radiation (LDR) in DMBA-induced mammary gland carcinoma in female rats. DMBA-induced mammary gland carcinoma as marked by an elevation of mRNA level of cancer promoter genes (Serpin and MIF, LOX-1, and COL1A1) and serum level of VEGF, TNF-α, TGF-β, CA15-3, and caspase-3 with the reduction in mRNA level of suppressor gene (FST and ADRP). These deleterious effects were hampered after treatment with BM-MSCs (1 × 10 6 cells/rat) once and daily administration of SeNPs (20 mg/kg body weight) and exposure once to (0.25 Gy) LDR. Finally, MSCs, SeNPs, and LDR notably modulated the expression of multiple tumor promoters and suppressor genes playing a role in breast cancer induction and suppression.

Assessment of radiometric hazards in the Southern Industrial Zone, Jeddah City, using car-borne gamma-ray spectrometry system - Hussein M. Harbi; Helmy S. Abuenaga; Mohamed A. Rashed; Ali H. Atef (Arabian Journal of Geosciences, 2022)

Four new phenolics and antiparasitic secondary metabolites from Flacourtia rukam Zoll. & Mortizi - Naglaa I. Afifi; Abeer S. Moawad; Mohamed A. Zaki; Mostafa E. Rateb; Mohammed H. Rashed; Ibrahim G. Saleh; Mona H. Hetta; Rabab M. Mohammed (Natural Product Research, 2022)

Ag nanoparticle-decorated chitosan/SrSnO3 nanocomposite for ultrafast elimination of antibiotic linezolid and methylene blue - M. Faisal; Md Abu Rashed; Jahir Ahmed; Mabkhoot Alsaiari; Mohammed Jalalah; Saeed A. Alsareii; Farid A. Harraz (Environmental Science and Pollution Research, 2022)

Potential aptitude of four olive cultivars as anticancer and antioxidant agents: oleuropein content - Shimaa A. Rashed; Tamannouha I. Saad; Salama M. El-Darier (Rendiconti Lincei. Scienze Fisiche e Naturali, 2022)
Olea europaea L. (olive, Oleaceae) constitutes a source of many bioactive compounds, which have recognized benefits for both human health and technological purposes. The present article was carried out to evaluate the biological activity of oleuropein (an ester of 2-(3,4-dihydroxyphenyl) ethanol (hydroxytyrosol) which has the oleosidic skeleton that is common to the secoiridoid glucosides of Oleaceae). It occurred in leaf extracts of the four olive cultivars (Chemlali, Manzanilla, Picaul and Toffahi) as a source for some anticancer and antioxidant agents and their consequences on the action of Hordeum vulgare (barley). The total phenolic and flavonoid compounds were extracted from olive leaves by ethanol 95% then analyzed by high-performance liquid chromatography (HPLC). The study evaluates the anticancer activity of the ethanolic extract of olive leaves against breast and hepatocellular carcinoma cells showing high values. Also, the extract exhibited highly consequence on the antioxidant potentiality of barley which was assessed using the diphenyl picryl hydrazyl method (DDPH). These results pave the way for utilization of olive leaves as a source of natural anticancer and antioxidant agents.

A Roadmap for Policy-Relevant Sea-Level Rise Research in the United Arab Emirates - Hannah Melville-Rea; Clare Eayrs; Nasser Anwahi; John A. Burt; Denise Holland; Fatin Samara; Francesco Paparella; Ahmed Hassan Al Murshidi; Maryam Rashed Al-Shehhi; David M. Holland (Frontiers in Marine Science, 2021)
The United Arab Emirates (UAE) has a long-term policy horizon, the financial capital, and a vision for a sustainable knowledge-based economy. These characteristics uniquely situate it as a potential leader for sea-level rise research. Climate science is already growing, and at the center of the UAE's pivot toward climate research is a burgeoning concern for sea-level rise. Over 85% of the UAE's population and more than 90% of the nation's infrastructure is within a few meters of present-day sea-level. With its low-lying and shallow-sloping geography (about 35 cm per km), this high-value coastline, including the rapidly expanding cities of Dubai and Abu Dhabi, is particularly vulnerable to sea-level rise. Meanwhile, limited regional research and data scarcity create deep uncertainty for sea-level projections. We set out a potential roadmap for the UAE to capitalize on its strengths to create usable and relevant sea-level projections for the region. With a newly established Climate Change Research Network, the UAE government is beginning to draw together universities and research centers for “furthering effective data collection and management, and advancing policy-relevant research on climate impacts and adaptation 1 .” By consolidating ideas from the science community within the UAE, we identify promoters and barriers to data gathering, information sharing, science-policy communication, and funding access. Our paper proposes pathways forward for the UAE to integrate sea-level science with coastal development and form best practices that can be scaled across climate science and throughout the region.

Treatment of hepatitis C virus infection with direct-acting antivirals plus ribavirin eliminates viral RNA from peripheral blood mononuclear cells and reduces virologic relapse in diverse hepatic parenchymal changes - Mohamed Darwish Ahmed Abd Alla; Reham M. Dawood; Hassan Abd EL-Hafeth Rashed; Galal Farrag; Islam Abdelmawla Emran Ammar; Mohamed Mahmoud Abdel-Halim Mahmoud; Ghada M. Salum; Ahmed Mohamed Abdulhamid Altanbouly; Mai A. El Meguid; Mostafa K. El Awady (Archives of Virology, 2021)

Development of potential map for groundwater abstraction in the northwest region of Bangladesh using RS-GIS-based weighted overlay analysis and water-table-fluctuation technique - Sara Nowreen; Imran Hossain Newton; Rashed Uz Zzaman; A. K. M. Saiful Islam; G. M. Tarekul Islam; Md. Saiful Alam (Environmental Monitoring and Assessment, 2021)

Repurposing of Secukinumab as Neuroprotective in Cuprizone-Induced Multiple Sclerosis Experimental Model via Inhibition of Oxidative, Inflammatory, and Neurodegenerative Signaling - Amany El-Shahawy Abdel-Maged; Amany M. Gad; Laila Ahmed Rashed; Samar S. Azab; Eman A. Mohamed; Azza S. Awad (Molecular Neurobiology, 2020)

Highly effective surface modification using plasma technologies toward green coloration of polyester fabrics - Fatma Abdelghaffar; Rehab A. Abdelghaffar; Usama M. Rashed; Hend M. Ahmed (Environmental Science and Pollution Research, 2020)

Imaging contamination surrounding a wastewater dumpsite using 2 terrain conductivity meters - Mohamed A. Rashed; Hussein M. Harbi; Burhan A. Niyazi; Ali H. Atef (Arabian Journal of Geosciences, 2020)

TP53 genetic polymorphisms and susceptibility to cervical cancer in Bangladeshi women: a case–control study - Mohd Nazmul Hasan Apu; A. Z. M. Rashed; Tafsir Bashar; Md Morshadur Rahman; Md Shaki Mostaid (Molecular Biology Reports, 2020)

Rutin inhibits carfilzomib-induced oxidative stress and inflammation via the NOS-mediated NF-κB signaling pathway - Naif O. Al-Harbi; Faisal Imam; Mohammed M. Al-Harbi; Othman A. Al-Shabanah; Moureq Rashed Alotaibi; Homood M. As Sobeai; Muhammad Afzal; Imran Kazmi; Ammar Cherkess Al Rikabi (Inflammopharmacology, 2019)

Preparation and Characterization of Biomass Carbon–Based Solid Acid Catalysts for the Esterification of Marine Algae for Biodiesel Production - Azeem Rana; Mohammed S. M. Alghazal; Mohammed M. Alsaeedi; Rashed S. Bakdash; Chanbasha Basheer; Abdulaziz A. Al-Saadi (BioEnergy Research, 2019)

Spatiotemporal trends in freshwater availability in the Red Sea Hills, Saudi Arabia - Burhan A. Niyazi; Mohamed Ahmed; Jalal M. Basahi; Milad Z. Masoud; Mohamed A. Rashed (Arabian Journal of Geosciences, 2018)

Effects of Holding Temperatures on the Development of Zebra Chip Symptoms, ‘Candidatus Liberibacter Solanacearum’ Titers, and Phenolic Levels in ‘Red La Soda’ and ‘Russet Norkotah’ Tubers - C. M. Wallis; A. Rashed; F. Workneh; L. Paetzold; C. M. Rush (American Journal of Potato Research, 2017)

Experimental assessment of non-edible candlenut biodiesel and its blend characteristics as diesel engine fuel - H. K. Imdadul; N. W. M. Zulkifli; H. H. Masjuki; M. A. Kalam; M. Kamruzzaman; M. M. Rashed; H. K. Rashedul; Azham Alwi (Environmental Science and Pollution Research, 2017)

Conjugate Heat Transfer in an Annulus with Porous Medium Fixed Between Solids - Irfan Anjum Badruddin; Salman Ahmed N. J.; Abdullah A. A. A. Al-Rashed; N. Nik-Ghazali; Mohammed Jameel; Sarfaraz Kamangar; H. M. T. Khaleed; T. M. Yunus Khan (Transport in Porous Media, 2015)

Petrology, geochemistry and remote sensing data of island arc assemblage along Wadi Abu Marawat, Central Eastern Desert, Egypt - A. M. Asran; R. Kh. Bekir; E. Abdel Rahman; A. Abdel El-Rashed (Arabian Journal of Geosciences, 2013)

Effect of recombinant erythropoietin on ischemia–reperfusion-induced apoptosis in rat liver - Heba M. Shawky; Sandra M. Younan; Leila A. Rashed; Heba Shoukry (Journal of Physiology and Biochemistry, 2012)

Analysis of Heat and Mass Transfer in a Vertical Annular Porous Cylinder Using FEM - Irfan Anjum Badruddin; N. J. Salman Ahmed; Abdullah A. A. A. Al-Rashed; Jeevan Kanesan; Sarfaraz Kamangar; H. M. T. Khaleed (Transport in Porous Media, 2012)

Effects of streptozotocin-induced long-term diabetes on parietal cell function and morphology in rats - Salim M. A. Bastaki; Ernest Adeghate; Irwin S. Chandranath; Naheed Amir; Saeed Tariq; Rashed S. Hameed; Abdu Adem (Molecular and Cellular Biochemistry, 2010)

Screening for tetracycline residues in food products of animal origin in the State of Kuwait using Charm II radio-immunoassay and LC/MS/MS methods - Hani M. Al-Mazeedi; Alaa B. Abbas; Hussam F. Alomirah; Wafaa Y. Al-Jouhar; Siham A. Al-Mufty; Mohamed M. Ezzelregal; Rashed A. Al-Owaish (Food Additives & Contaminants: Part A, 2010)

Gastroprotective and antisecretory effects of Ailanthus excelsa (Roxb) - Larissa S. Melanchauski; Ana Paula G. S. Broto; Thiago M. Moraes; Ana Lúcia M. Nasser; Ataa Said; Usama W. Hawas; Khaled Rashed; Wagner Vilegas; Clélia A. Hiruma-Lima (Journal of Natural Medicines, 2010)

Multiple dolomitization events of the Lower Carboniferous Um Bogma Formation, west central Sinai, Egypt - M. N. Shaaban; H. M. Holail; K. N. Sedeik; M. A. Rashed (Carbonates and Evaporites, 2005)

Dolomitization of middle miocene buildups, Um Gheig area, Red Sea coast, Egypt - Mohamed N. Shaaban; Hanafy M. Holail; Mohamed A. Rashed (Carbonates and Evaporites, 1997)